Relationship Between Age, Gender, Job Placement, and Social Relationships with the Mental Workload of Managers - Priskila Hananingrum; Ais Assana Athqia; Y. Denny A. Wahyudiono (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Mental workload is one of the most important aspects that affects the health and safety of workers. The Maintenance and Repair Division and Warship Division are divisions in PT. PAL which has a high job demand of the workers in it. Methods: This study was an observational analytic study with a cross-sectional design. The independent variables used in this study were age, gender, job placement, and social relationship, while the dependent variable was mental workload. The sample used was the total population of all managers in both divisions, totaling 12 respondents. The data was collected using a general questionnaire and the NASA-TLX method was used to measure mental workload. The data analysis technique used was the correlation test. Results: In the Maintenance and Repair Division, most managers were in the age range of 46 – 55 years old (50%) and 4 managers had an overloaded mental workload (66.7%). In the Warship Division, most of the managers were 46 – 55 years old (66.6%) and 4 managers (66.7%) had a moderate workload. Age has a relationship with mental workload in the Maintenance and Repair Division (0,612) and Warships Division (-0,316). Gender shows no relation with mental workload in the Warship Division (0,196). Job placement (-0.632) and social relationship (0.316) have a relation with mental workload in the Warship Division. Conclusion: Age has a relationship with mental workload in both divisions while there is no relationship between gender and mental workload among the managers in the Warship Division. Job placement has a strong negative relationship while social relationship has a strong positive with the mental workload in the Warship Division.